2020
DOI: 10.1111/jonm.12914
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary understanding of nurses’ workplace social capital: A response to the rapid changes in the nursing workforce

Abstract: Aim To provide an updated definition of the concept of nurses’ workplace social capital that addresses changes in the contemporary nursing workforce. Background Social capital explains the components of a constructive work environment. Advancements in psychology of workplace and changes in the demographic structure of nursing workforce call for a revised version of nurses’ workplace social capital. Method Walker and Avant's approach was implemented. Data were compiled from ‘Medline’ and ‘CINAHL’, ‘Google’ sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 42 publications
(106 reference statements)
0
41
0
Order By: Relevance
“…Owing to the sudden onset and uncertainty of the epidemic, many did not know whether or how to discuss their feelings of stress with their colleagues and did not seek help from their existing social networks, and because workplace social capital was relatively low during the early period of the outbreak, nurses failed to regulate the negative effects of perceived stress on their professional identity (Petropoulos & Makridakis, 2020; Sarfraz et al, 2019; Xu, Xu, Wang, & Wang, 2020). Furthermore, it should be noted that the effects of psychological factors on professional identity are actually best understood as a long‐term process, but the present study only took samples from clinical nurses during the early stages of the epidemic (Sehmi et al, 2019; Wang, Li, Wang, Chu, & Xu, 2011; Xu, Kunaviktikul, Akkadechanunt, Nantsupawat, & Stark, 2020a). As a result of this study's brief duration, it may not have accurately observed how workplace social capital affects professional identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the sudden onset and uncertainty of the epidemic, many did not know whether or how to discuss their feelings of stress with their colleagues and did not seek help from their existing social networks, and because workplace social capital was relatively low during the early period of the outbreak, nurses failed to regulate the negative effects of perceived stress on their professional identity (Petropoulos & Makridakis, 2020; Sarfraz et al, 2019; Xu, Xu, Wang, & Wang, 2020). Furthermore, it should be noted that the effects of psychological factors on professional identity are actually best understood as a long‐term process, but the present study only took samples from clinical nurses during the early stages of the epidemic (Sehmi et al, 2019; Wang, Li, Wang, Chu, & Xu, 2011; Xu, Kunaviktikul, Akkadechanunt, Nantsupawat, & Stark, 2020a). As a result of this study's brief duration, it may not have accurately observed how workplace social capital affects professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, good relationships with leaders, colleagues and patients, as well as a pleasant workplace atmosphere, can help relieve pressure on nurses and alleviate the harmful effects of perceived stress on professional identity (Kılıç & Altuntaş, 2019). Furthermore, a high‐quality workplace social capital not only benefits clinical nurses, but also could improve the quality of patient care and promote changes in hospital management (Chang, Huang, Chiang, Hsu, & Chang, 2012; Ernstmann et al, 2009; Jafari, Pourtaleb, & Khodayari‐Zarnaq, 2018; Shin & Lee, 2016; Spence Laschinger, Read, Wilk, & Finegan, 2014; Xu, Kunaviktikul, et al, 2020a). Thus, whether during COVID‐19 outbreaks or in daily nursing management, workplace social capital is a useful resource that managers can implement and leverage to improve positive outcomes for both the department and its nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The overall climate of an organization is an umbrella term that reflects a core set of values and behaviors which permits implementation of evidence‐based recommendations about human resource management and organizational design 22 . The concept of micro‐climate refers to the milieu within various entities, that is, wards and division units, where the effectiveness of the nursing leadership primarily demonstrated through the social capital at the workplace 41 . The concept of social capital reflects a relational network among the nursing workforce within each specific work entity; this relational network is configured by respect, trust, and reciprocity among the nursing professionals.…”
Section: Implications For the Nursing Workforcementioning
confidence: 99%
“…Meanwhile, nurses' workplace social capital can be classi ed into three types, bonding, bridging, and linking. Bonding and bridging in the context of social capital describe relationships established within and/or among groups at the same professional and power level and, therefore, is regarded as horizontal social capital; in contrast, linking social capital represents relationships across different strata of power and is considered vertical social capital [4,14,21]. The diagram of the constitution of this focal concept is depicted in Fig.…”
Section: The Focal Concept Of the Conceptual Modelmentioning
confidence: 99%
“…Research portends the positive and promising in uences of nurses' workplace social capital [3,4]. The value of ndings from single studies is nil if the knowledge gained is not integrated into a network to present a more comprehensive understanding of the reported phenomenon [5,6].…”
Section: Introductionmentioning
confidence: 99%